A generation gap between children and their parents in Pashtun community Buner District, Khyber Pakhtunkhwa, Pakistan - Pir Wahab; Shamas Ud Din; Kinan Pasha; Mukhtar Ahmed; Mujahid Hussain; Jamil Khan (Faculty of Social and Political Science, Universitas Airlangga, 2022)
The generation gap is a serious, challengeable problem in the emerging society in Pakistan. It refers to parents or elders’ disagreements, conflicts, inconsistencies, and differences in several matters such as attitude, behaviour, beliefs, values, politics, closeness, modern technology, cultural changes, and communication. The present study was designed to analyse the causes and consequences of the generation gap among the Pashtun community. A quantitative research method was used to select 400 samples of the current population and collect data through a well-designed questionnaire. The validity and reliability of the questionnaire were examined by ten PhD scholars from different universities. The Cronbach’s Alpha for the data is .969. The data was analysed using SPSS version 26. The results were shown in the form of a one-way ANOVA and a frequency distribution table. The data revealed a statistically significant (0.05) relationship between various variables such as technological advancement, living patterns, behaviour, social norms, communication gaps, unemployment, poverty, socioeconomic status, and religiosity. Both parents and children are responsible for the generation gap, but it can be reduced by understanding, loving, caring, sharing, communicating, and maintaining friendly relations.